-5x = 3 - 9x add 9x to both sides, which gives you: 4x = 3 divide 4 on both sides, giving you: x = 3/4 or 0.75 I hope this helps!
-5x = 3 - 9x add 9x to both sides, which gives you: 4x = 3 divide 4 on both sides, giving you: x = 3/4 or 0.75 I hope this helps!
p - 5 - 13p = 150 - 11 By combining like terms, you get: -12p - 5 = 139 Next, you add 5 to both sides, giving you: -12p = 144 Now, divide both sides by -12, giving you a final answer of: p = -12 Hope this helps!
(2x+4)2 = (2x+4)(2x+4) Use the FOIL method: First, Outer, Inner, Last: First: 2x•2x = 4x2 Outer: 2x•4 = 8x Inner: 2x•4 = 8x Last: 4•4 = 16 Which gives you: 4x2+8x+8x+16 Combine like terms: 4x2+16x+16 Hope this helps...
This equation simply means to subtract 10x-3x, which gives you 7x. If the equation is 10x2-3x, factor out an x, giving you x(10x-3). I hope this helps!
6x+5+3x=50, add the common terms together: 6x+3x=9x, so 9x+5=50 Then, subtract 5 from both sides, which gives you 9x=45. From here, divide 9 on both sides, giving you x=5. I hope this helps!
The negative sign needs to be applied to each term, so -(9x-3) = -9x+3 Then, you can divide 3 from both terms, so -9x+3 = -3(3x-1) I hope this helps!
You can approach this from a few different ways. I would set the second equation to be: x=y+2 Then, take the above equation and plug it into the x variable in the first equation. Now, the equation should be: y+2+y=-12. Simplifying, 2y=-14. 2 divided by -14 equals -7, so...